Procurement and maintenance of facilities and infrastructure in inclusive schools - Dwi Yoswita Fertika; Sowiyah Sowiyah; Hasan Hariri (Lighthouse Publishing, 2022)
Inclusive education ensures that students with mental and physical disabilities have equal access to regular schooling alongside their peers. Inclusive education aims to reduce prejudice toward children with disabilities. The purpose of this study was to investigate the planning, procurement, and maintenance of SMAN 14 Bandar Lampung's facilities and infrastructure. A descriptive qualitative method was adopted in this study, and data were collected from the school principal, vice-principal for student affairs, vice-principal for curriculum and academic affairs, vice-principal for facilities and infrastructure, vice-principal for public relations, school teachers, students' parents, students, and stakeholders. Observation, interviews, and document studies were used to collect data. The findings indicated that the provisions were used to procure and maintain the school's facilities and infrastructure. Routine, periodic, preventive, and repressive maintenance of facilities and infrastructure is performed, with procurement of facilities and infrastructure occurring once a year. Finally, the procurement and maintenance of infrastructure at the school under investigation were carried out in accordance with the plan established under existing provisions. Schools must maintain the quality of their facilities and infrastructure in order to remain operational.